The Marine Polyketide Myriaporone 3/4 Stalls Translation by Targeting the Elongation Phase. Issue 2 (9th January 2013) - Muthukumar, Yazh; Roy, Myriam; Raja, Aruna; Taylor, Richard E.; Sasse, Florenz
Abstract Myriaporone 3/4, a cytotoxic polyketide, has been reported as an inhibitor of eukaryotic protein synthesis. However, the mechanism by which it inhibits translation was unknown. Here we show that myriaporone 3/4 stalls protein synthesis in the elongation phase by inducing phosphorylation of eukaryotic elongation factor 2. The phosphorylation results from direct binding of myriaporone 3/4 to eukaryotic elongation factor 2 kinase. Our study also shows that myriaporone 3/4 in the nanomolar range inhibits in vitro tube formation by endothelial cells without being cytotoxic. In general, myriaporone 3/4 was at least 300 times less toxic to primary cells than to tumor cells.